PENDAPATAN USAHA DAN PERSEDIAAN BAHAN BAKU INDUSTRI BAWANG GORENG (Studi Kasus Industri Bawang Goreng “Uda Saprudin”) - Herlena Bidi Astuti; Yesmawati Y; Linda Harta; Reswita R (AGRIBUSINESS JOURNAL, 2019)
Processing shallots into fried onions is one of the agro-industry businesses with the main raw material of shallots. The fried onion home industry is a downstreaming of agricultural commodities by providing added value from the raw materials of shallots, in the process of production competition the industry must conduct management that will produce raw materials to ensure obtaining products. The purpose of this study was to determine the operating income of fried onions and determine the management of raw materials in the "Uda Saprudin" fried onion industry in Bengkulu City. The method used in this study is the calculation of income, R / C ratio, and management of raw materials using EOQ, Safety Stock, Reorder Points, lead time and total inventory costs. This research is a case study conducted in February 2019 with the data used is the data of the past year (2018). From the research results obtained R / C value of 1.36 and the management of raw material requirements recognized EOQ value: 6.546 Kg, Reorder Point value: 6.329 Kg / Month, lead time: 0.5 months and Total inventory costs: Rp. 163,676,047 per year.